Managing Human Resources in Public Health Care System in South Asia: Case Study of Pakistan. (June 2016) - Suhail, Aneeqa; Azhar, Aisha
Health care is considered as one of the fundamental rights of every individual. At the same time, efficient and effective delivery of health care service requires pro-active management of health care professionals. The purpose of this article is to highlight human resource issues and challenges faced by health care professionals in South Asia and identify suitable strategies for better management of health care professionals. By using data from a pilot study in Pakistan's public health sector in the province of Punjab, the article explores ways of implementing productive reforms to upgrade human resource management system in the public health care sector in South Asian countries.